Customer satisfaction levels towards public bus services in Kuantan, Pahang - Bung, Yi Xian; Melan, Mustakim (2012)
Back to the recent few years, the service industry has progressively plays essential role in the countries’ economy. Many of the service companies are focused on the service quality and the consumer satisfaction. Despite of private sectors, the public sector organization has increasingly focused on customer satisfaction levels so that can increased its competitiveness and service quality. Public transportation is recognized as low cost, safe and time saving method to travelling around the city.However, the utilization rate of public buses in Kuantan is lower than other cities in Malaysia.The paper will extracts on board passenger survey to conduct the evaluation of customer satisfaction levels towards public bus services in Kuantan in terms of product and service strategies, driver’s behavior and bus facilities.The findings will help in enhance the service quality of public buses in Kuantan and fulfilling passenger’s needs.